Penggunaan Metode Discovery Learning untuk Meningkatkan Hasil Belajar Peserta Didik - Rachmawaty, Shella (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2024)
The Discovery Learning method is a learning method that emphasizes the active role of students in the learning process. This research is a class action research with research subjects being students of class X Culinary 2 SMK Negeri 1 Kota Tangerang Selatan. This research was conducted in two cycles using learning achievement test instruments and observing student participation during the learning process. The results showed that the use of the Discovery Learning method significantly increased student learning outcomes and increased active participation of students in the learning process, which was proven by the average student learning outcomes in cycle I, there were 14 students with complete information with a percentage of 38, 9%, and there were 22 students with incomplete information with a percentage of 61.1% with an average grade of 66. From the results of the learning completeness percentage, the level of learning completeness is included in the Low category. Whereas in cycle II there were 32 students with complete information with a percentage of 88.9%, and there were 4 students with incomplete information with a percentage of 11.1% with an average grade of 82.8. From the results of the learning completeness percentage, the learning completeness level is included in the Very High category. Therefore, the Discovery Learning learning method can be recommended as an alternative and solution in a more effective learning process.